Survey of Gravitationally Lensed Objects in HSC Imaging (SuGOHI) – VII. Discovery and confirmation of three strongly lensed quasars. Issue 1 (20th January 2021) - Jaelani, Anton T; Rusu, Cristian E; Kayo, Issha; More, Anupreeta; Sonnenfeld, Alessandro; Silverman, John D; Schramm, Malte; Anguita, Timo; Inada, Naohisa; Kondo, Daichi; Schechter, Paul L; Lee, Khee-Gan; et al.
ABSTRACT: We present spectroscopic confirmation of three new two-image gravitationally lensed quasars, compiled from existing strong lens and X-ray catalogues. Images of HSC J091843.27–022007.5 show a red galaxy with two blue point sources at either side, separated by 2.26 arcsec. This system has a source and a lens redshifts z s = 0.804 and z ℓ = 0.459, respectively, as obtained by our follow-up spectroscopic data. CXCO J100201.50+020330.0 shows two point sources separated by 0.85 arcsec on either side of an early-type galaxy. The follow-up spectroscopic data confirm the fainter quasar has the same redshift with the brighter quasar from the Sloan Digital Sky Survey (SDSS) fiber spectrum at z s = 2.016. The deflecting foreground galaxy is a typical early-type galaxy at a redshift of z ℓ = 0.439. SDSS J135944.21+012809.8 has two point sources with quasar spectra at the same redshift z s = 1.096, separated by 1.05 arcsec, and fits to the HSC images confirm the presence of a galaxy between these. These discoveries demonstrate the power of the Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP)'s deep imaging and wide sky coverage. Combined with existing X-ray source catalogues and follow-up spectroscopy, the HSC-SSP provides us unique opportunities to find multiple-image quasars lensed by a foreground galaxy.